STRATEGI PENDAMPINGAN BIMBINGAN ROHANI ISLAM BAGI KELUARGA PASIEN KRITIS MELALUI PENDEKATAN EMPATIK DI RS PKU MUHAMMADIYAH PETANAHAN - Putri Ananda Dewi Kusuma; Vinka Firstyandani (Counseling For All : Jurnal Bimbingan dan Konseling, 2025)
This study is motivated by the high level of psychological stress experienced by families of critically ill patients at RS PKU Muhammadiyah Petanahan. Such stress often manifests as anxiety, fear, uncertainty, and excessive worry related to the health conditions of their family members. These circumstances not only affect the psychological well-being of the families but also have the potential to hinder the optimal support they can provide to the patients. Therefore, an effective accompaniment strategy is needed one that can provide reassurance, guidance, and spiritual strengthening to the patients’ families. The aim of this study is to analyze the spiritual guidance accompaniment strategies based on an empathic approach applied by spiritual guidance officers at the hospital. A descriptive qualitative research method was employed, with data collected through direct observation and in-depth interviews with spiritual guidance officers as primary sources of information. The research instruments included observation and interview guidelines designed to explore the processes, techniques, and effectiveness of the accompaniment strategies. The findings indicate that empathic accompaniment strategies are highly effective in alleviating psychological stress among patients’ families. These strategies include active listening, using calming language, building emotional closeness, providing spiritual motivation, and adjusting the approach according to each family’s emotional condition. This approach not only fosters mental calmness and resilience but also enhances the families’ reliance on Allah SWT, enabling them to face critical situations with greater serenity and acceptance. These findings underscore the importance of integrating empathic spiritual guidance into healthcare services to support the psychological well-being of families of critically ill patients.